Commercial exploitation threatens Iriartea deltoidea and Wettinia quinaria in Northwestern Ecuador - Altamirano Acuña, Diana Carolina (2012)
In Ecuador, the conservation of natural forests is regulated by dozens of_x000D_ environmental laws (e.g., CITES, 1973; Ley Forestal, 1981; MAE, 2001; see de la Torre et_x000D_ al., 2011). In practice, however, the effectiveness of these regulations is doubtful: the_x000D_ country suffers a 1.8% annual loss of native forest (from 2000 to 2010), which is the_x000D_ highest deforestation rate reported for South America (FAO, 2010). In fact, from 1990 to_x000D_ 2008, 12,375 km2 of forests were depleted from Ecuador (4.5 % of the territory; MAE,_x000D_ 2011). Clearly, regulations and policies intended to develop rural areas and to strengthen_x000D_ the economy have been prioritized over those intended to conserve nature. As for instance,_x000D_ the agrarian reform and colonization law (in force between 1964 and 1994), and policies_x000D_ enacted to develop the national road network (in the mid-1980s, and early 2000s, e.g.,_x000D_ CONADE, 1985; MOP, 2002) have promoted forest fragmentation and countrywide_x000D_ deforestation (Añazco et al., 2010; Falconí and Burneo, 2005). One alternative to slow_x000D_ down deforestation may be the sustainable use (maintenance of viable and healthy_x000D_ populations of species that are harvested by humans) of non-timber forest products_x000D_ (NTFPs), whose commercialization may also provide...